Zoonotic Diseases Associated with Encephalitis - ., Darminto; Bahri, Sjamsul; Saepulloh, Muharam (Indonesian Animal Sciences Society, 1999)
Outbreak of encephalitis, which killed more than 80 people in Malaysia, invited public attention throughout the world, especially stakeholders in animal husbandry and veterinary practices. The disease was initially diagnosed as Japanese-B- encephalitis (JE) which was transmitted to human from infected pigs. Recently, the causal agent of the outbreak has been identified as morbilivirus which was called Hendra-like Virus or Nipah Virus. Indonesia as neighboring country to Malaysia needs to take anticipation to prevent the occurrence of similar outbreak. For anticipation, it is required to understand all diseases, which cause encephalitis, especially the zoonotic diseases. From many infectious diseases of animal, only 17 diseases which are able to cause encephalitis, 9 of them are zoonotic diseases: Eastern equine encephalomyelitis (EEE), Western equine encephalomyelitis (WEE), Venezuelan equine encephalomyelitis (VEE), Japanese-B-encephalitis (JE), Murray valley encephalitis (MVE), Louping-ill, Rabies and Equine morbilivirus (EMV) and Nipah Virus. The viral agents and the mode of transmission to human are discussed in this publication. All those encephalitic zoonoses, except Rabies and JE, are exotic to Indonesia. So it is required to keep the free status of Indonesia to those diseases by strict quarantine measures. All imported animals to Indonesia should be confirmed free from those diseases based on the laboratory examination. Key words: Encephalitis, zoonosis, nipah virus